A música local na escola cearense: uma análise sobre as trajetórias de formação docente - Parente, Filipe Ximenes (2015)
This study analyzed the trajectory of three students of the degree course in Music of the Federal University of Ceará (UFC) to the time when the educational project entitled "local music school in Fortaleza," was presented to the said students in the discipline of supervised. For such studies, we focused on the training process, the accumulation of capital and the work with the local music. We consider primarily the interviews, in order to analyze the trajectory of training of students cited; order to identify what capital they have accumulated during their training, which became advantages and / or disadvantages in their teaching practice with the Ceará music, and field observation. The analysis and interpretation of data were made with theoretical and methodological contribution of theorists such as Zoltan Kodály, which is used as main repertoire local music on your music education project; Keith Swanwick, to analyze the musical practices; and the concepts of habitus, field and capital Pierre Bourdieu, who provided us with the conceptual contribution needed to understand the formation of the teaching practice of the subjects of this research.